Diseño de un sistema de gestión de calidad, basado en las normas ISO 9001:2008, para la empresa Gyba Medica distribuidora de medicamentos a través del portal de compras públicas. - Arévalo Barrionuevo, Mariana Elizabeth (2015)
The aim of this thesis is to design a quality management system based on Iso International Standards 9001:2008 for the enterprise “GYBA MEDICA”, considering its current situation and the internal analysis of the company in order to identify its performance and operability. It also analyzes external factors of the organization such as: inflation, political and social factor, the external customer, competitors and providers. With this information the EFE matrix is done where opportunities and threats are identified in order to generate solutions. The company processes and the proper performance of each one were identified, it was done based on the analysis to structure the Quality Management System based on ISO 9001: 2008. In order to carry out with the ISO standards, the policy and quality objectives were defined. Finally, the financial study shows a projected balance sheet where is compared the implementing of the quality management system in the enterprise and if it’s not implemented, the objective is to visualize the economic profits that will give to the enterprise, the right implementation of the quality management system.